2017
DOI: 10.1002/ange.201710601
|View full text |Cite
|
Sign up to set email alerts
|

Macrolide Synthesis through Intramolecular Oxidative Cross‐Coupling of Alkenes

Abstract: AR h III -catalyzed intramolecular oxidative crosscoupling between double bonds for the synthesis of macrolides is described. Under the optimizedreaction conditions,macrocycles containing ad iene moiety can be formed in reasonable yields and with excellent chemo-and stereoselectivity.T his method provides an efficient approach to synthesize macrocyclic compounds containing a1,3-conjugated diene structure.Scheme 1. Synthesis of macrocyclic compounds containing a1,3-conjugated diene moiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…NaBAr F may perform as a cocatalytic additive to generate the cationic palladium species via anion exchange of weakly coordinating BAr F − with chloride ions in PdCl 2 . 18 Next, different pyridineoxazoline-type ligands were investigated to further improve the yield and the stereoselectivity (Scheme 2). After screening various substituents at the 3-, 4-, 5-, and 6-positions of the pyridine moiety, L10 with the −CF 3 group at the 5-position was optimal (L1−L15).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…NaBAr F may perform as a cocatalytic additive to generate the cationic palladium species via anion exchange of weakly coordinating BAr F − with chloride ions in PdCl 2 . 18 Next, different pyridineoxazoline-type ligands were investigated to further improve the yield and the stereoselectivity (Scheme 2). After screening various substituents at the 3-, 4-, 5-, and 6-positions of the pyridine moiety, L10 with the −CF 3 group at the 5-position was optimal (L1−L15).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This highly efficient cross coupling is illustrated by the example below (Scheme 18). The mechanism presented below is slightly different from the mechanism proposed by Jiang et al 80 As a result of kinetic isotope effect (KIE) studies, 80 it was proposed that the active catalyst [Cp*Rh (OAc)][BARF] coordinates to the enamide moiety by oxidative insertion (removal) of the syn-hydrogen (syn to the amide carbonyl i.e. H b ) to yield (73).…”
Section: Oxidative Generation Of Radical Cations In Pseudomacrocyclicmentioning
confidence: 85%
“…Jiang et al, 80 has also reported a rather different Rh catalyzed macrocyclization via oxidative cross coupling of the olenic moieties. This highly efficient cross coupling is illustrated by the example below (Scheme 18).…”
Section: Oxidative Generation Of Radical Cations In Pseudomacrocyclicmentioning
confidence: 99%
“…The first intramolecular Rh(III)-catalysed oxidative crosscoupling reaction between two C(sp 2 )-H bonds was reported by Xu and Loh in 2018 (Scheme 2). 14 Macrolides bearing a Z,E-1,3-diene conjugated configuration were afforded by selective Z-vinyl C-H bond activation. The alkenyl C-H bond cleavage was suggested to be the rate-determining step by kinetic studies.…”
Section: Alkene-alkene Couplingmentioning
confidence: 99%